From the Harvard Medical Practice Study to the Luxembourg Declaration. Changes in the approach to patient safety. Closing remarks (Italian Journal of Public Health, 2005)
Since the Harvard Medical Practice Study was published in 1991 the growing mass of international literature has demonstrated that medical adverse events can cause iatrogenic illnesses, prolonged hospitalisations and increased costs. In 1999-2001, reports made by the Institute of Medicine (IOM) in the USA, the Department of Health (DoH) in the UK and the Australian Patient Safety Foundation (APSF) stressed the necessity for creating a safer environment and a reporting culture throughout healthcare systems. They also emphasized the need for researchers to investigate means of turning policies into practice. Since their publication a lot of effort has gone into collecting data on adverse events and near misses. As a result, in 2001, the AHRQ published a Health Technology Assessment report on best practices for patient safety. While in Australia national meetings have been dedicated to address important issues across the whole spectrum of healthcare. In the UK the Audit Commission has published a report that is also focused on medication safety: “A spoonful of sugar”. In 2004 the World Health Organisation promoted a Patient Safety Alliance; while in April 2005the Standing Committee of European Doctors organised a Conference in Luxembourg called “Patient safety - Making it happen!”. The issue of patient safety is therefore seen as a priority by EU institutional bodies and by many European health stakeholders.
Keywords: Patient safety; adverse events; medical errors